Analisis Kemampuan Pemecahan Masalah Matematika Siswa SMP Kelas VII Pada Materi Bilangan Bulat - Dewi, Nurvani Yulia; Salsabillah, Aminda; Wahyuni, Reni (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to examine the mathematical problem-solving abilities of seventh-grade junior high school students on the topic of integers. A descriptive qualitative approach was employed, involving 36 students from a public junior high school in Kampar Regency. Data were collected through three specially designed written test items and semi-structured interviews to explore students' thinking processes. The results show that students’ abilities can be categorized into three levels: high (13.89%), moderate (69.44%), and low (16.67%). Students in the high category demonstrated systematic steps and critical reflection. Those in the moderate category generally understood the problems but often made mistakes in selecting and applying appropriate strategies and showed a lack of accuracy. Students in the low category struggled at almost every stage of problem-solving. Contributing factors include understanding of basic mathematical concepts, strategy selection, accuracy, and clarity of the problem statements. The study recommends the use of contextual and reflective learning approaches to enhance students' mathematical problem-solving skills. Keywords: Problem-solving, Integritas, Mathematics, Contextual learning.